High humidity alleviates photosynthetic inhibition and oxidative damage of tomato seedlings under heat stress - C. XU; Z.Q. YANG; S.Q. YANG; L. WANG; M.T. WANG (Photosynthetica, 2020)
This study investigated the effects of high humidity on the growth and photosynthetic and physiology traits of tomato plants under high temperature stress (HT). The results showed that high humidity effectively alleviated the limitation of HT on plant growth and increased the root-to-shoot ratio. In addition, high humidity also increased the chlorophyll content, net photosynthetic rate, and maximum photochemical quantum yield of PSII in tomato seedlings under HT stress, but declined the stomatal limitation value. Moreover, JIP-test showed that increasing air humidity improved the quantum yields and efficiencies of HT-stressed tomato plants and increased the size of functional antenna, while reduced the activity of a portion of reaction centers. Besides, high humidity increased the activity of antioxidant enzymes, but decreased the content of malondialdehyde and hydrogen peroxide in HT-stressed tomato plants. Therefore, high humidity improved the growth and alleviated photoinhibition and oxidative stress of tomato seedlings under heat stress.